2019
DOI: 10.1016/j.cub.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Elongation Phase of Protein Synthesis Enhances Translation Accuracy and Modulates Lifespan

Abstract: Graphical AbstractHighlights d eEF2 kinase enhances the accuracy of protein synthesis under a range of conditions d mTORC1 inhibition improves translation accuracy by activating eEF2K d eEF2K assists correct start codon selection during translation initiation d Impairing translation fidelity reduces lifespan in C. elegans In BriefXie et al. report that eukaryotic elongation factor 2 kinase (eEF2K), which impairs the rate of elongation, decreases misreading or termination readthrough errors and promotes the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 62 publications
4
65
0
Order By: Relevance
“…In contrast, the presence or absence of eEF2k did not affect the Fluc levels observed with the vector which has AUG as the start of the Fluc cistron ( Fig. S4A) which is in line with our earlier data [28].…”
Section: Eef2k Enhances Translation Of the Pd-l1 Mrna By Bypassing Trsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, the presence or absence of eEF2k did not affect the Fluc levels observed with the vector which has AUG as the start of the Fluc cistron ( Fig. S4A) which is in line with our earlier data [28].…”
Section: Eef2k Enhances Translation Of the Pd-l1 Mrna By Bypassing Trsupporting
confidence: 92%
“…The uORF partially overlaps with and inhibits the translation of the main ORF encoding PD-L1 [26]. We previously showed that activation of eEF2K helps reduce initiation at non-canonical start sites, i.e., CUG or GUG [28]. Impaired elongation slows down ribosomes within the main ORF and thus allows more time for selection of the optimal choice -an AUG start codon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell lysates were heated at 95°C for 5 min in Laemmli Sample Buffer and then subjected to sodium-dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE [29];) followed by electrophoretic transfer to 0.45 µm nitrocellulose membranes (Bio-Rad; 1620115). Membranes were blocked in PBS-0.05% Tween20 (PBST) containing 5% (w/ v) skim milk powder for 60 min at room temperature.…”
Section: Immunoblot Analysesmentioning
confidence: 99%